Les papiers de Baya Hocine. Une source pour l’histoire des prisons algériennes pendant la guerre d’indépendance (1954-1962) - Sylvie Thénault (L’Année du Maghreb)
In 1958, a search of the prison of Barbarossa in Algiers led to the confiscation of the Journal, notes and correspondence of Baya Hocine, a young female detainee of 17 years, sentenced to death for an attack. Written in the intimate style of a personal diary, Hocine’s papers are a valuable source for the historiography of prisons during the Algerian War of Independence (1954-1962). The purpose of this article is to reconstruct the trajectory from prison to the French Archives where they appear in typed form, as well as to elucidate the circumstances of their composition. While these are insufficient to reconstitute the material conditions of life in the prison due to their nature as private thoughts, they highlight the radical specificity of Barbarossa in these years of war as a place of detention and execution of those sentenced to capital punishment, in an atmosphere permeated with death.